Interleukin-1β-regulating antibody XOMA 052 (gevokizumab) in the treatment of acute exacerbations of resistant uveitis of Behçet's disease: an open-label pilot study. Issue 4 (14th November 2011) - Gül, Ahmet; Tugal-Tutkun, Ilknur; Dinarello, Charles A; Reznikov, Leonid; Esen, Bahar Artim; Mirza, Amer; Scannon, Patrick; Solinger, Alan
Abstract : Objective: Uveitis and retinal vasculitis are sight-threatening manifestations of Behçet's disease with limited treatment options. This pilot study aimed to evaluate the safety, pharmacokinetics and clinical activity of XOMA 052 (gevokizumab), a recombinant humanised anti-interleukin 1β antibody, in Behçet's disease patients with uveitis. Methods: Patients with acute posterior or panuveitis, and/or retinal vasculitis, resistant to azathioprine and/or ciclosporin, and receiving 10 mg/day or less of prednisolone, were enrolled into the 98-day study. Immunosuppressive agents were discontinued at baseline. Patients received a single infusion of XOMA 052 (0.3 mg/kg). The safety and uveitis status and pharmacokinetics of XOMA 052 were evaluated. Results: Seven patients enrolled and completed the study. No treatment-related adverse event was observed. XOMA 052 treatment was associated with rapid and durable clinical response in all patients. Complete resolution of intraocular inflammation was achieved in 4–21 days (median 14 days), with a median duration of response of 49 days (range 21–97 days); one patient remained exacerbation free throughout the study. Conclusions: Well tolerated, XOMA 052 resulted in a rapid onset and sustained reduction in intraocular inflammation in patients with resistant uveitis and retinal vasculitis. Moreover, the effect was observed despite discontinuation of immunosuppressive agents and without the need to increase corticosteroid dosages.